An examination of teacher collaboration in professional learning communities and collaborative teaching practices - Khasawneh, Yusra Jadallah Abed; Alsarayreh, Raghad; Ajlouni, Adnan Ahmad Al; Eyadat, Haitham Mustafa; Ayasrah, Mohammad Nayef; Khasawneh, Mohamad Ahmad Saleem (Journal of Education and e-Learning Research, 2023)
The present study aims to examine the influence of teacher collaboration within professional learning communities (PLCs) and collaborative teaching practices on both the professional growth and academic achievement of students. The study employed a mixed-methods research design that incorporated both qualitative and quantitative research methodologies. This research comprises both survey responses and interview transcripts obtained from K-12 educators who are currently engaged in Professional Learning Communities (PLCs) or collaborative teaching methodologies. The findings of this study have the potential to enhance the existing literature on teacher collaboration and furnish educators, policymakers, and researchers with valuable perspectives to steer optimal strategies for promoting effective teacher collaboration in Professional Learning Communities (PLCs) and collaborative teaching approaches. The objective of the research is to investigate the influence of teacher collaboration within Professional Learning Communities (PLCs) and collaborative teaching practices on the development of professional skills and academic achievements of students. The results of this study underscore the importance of recognizing the advantageous effects that collaborative teaching methodologies can have on the academic achievements of students. This necessitates the provision of adequate time for collaborative activities, encouraging supportive leadership within educational institutions, and allocating sufficient resources for collaboration.